Phase I clinical trial testing the dose escalation and expansion of Pressurized IntraThoracic Hyperthermic Aerosol Cisplatin administration (PITHAC) for the management of pleural carcinosis - Louis-Emmanuel Chriqui; Etienne Abdelnour-Berchtold; Edoardo Zanfrini; Severine Devesa-Perez; Michel Gonzalez; Thorsten Krueger; Kim Ellefsen; Alice Destaillats; David Bonnet; Martin Hübner; Hasna Bouchaab; Michal Bassani-Sternberg; et al. (Cancer Treatment and Research Communications)
Background: Pleural carcinosis originates from various cancers. Its management consists in systemic therapies combined to dyspnea relief procedures. Prior studies have tested hyperthermic intrathoracic chemotherapy to treat pleural carcinosis with interesting patient survival results. However, these approaches were limited by local toxicity. Pre-clinical data have shown that hyperthermia combined to local pleural chemotherapy increased the immune response against tumors. Recently, pressurized intraperitoneal aerosol chemotherapies (PIPAC) showed improved cytostatic penetration in abdominal carcinosis with a 10-fold-lower chemotherapy dose and minimal side-effects. This approach was also tested in limited numbers of patients with pleural carcinosis but never combined with hyperthermia. Methods: Pressurized IntraThoracic Hyperthermic Aerosol Cisplatin (PITHAC) is an open-label dose-escalation phase I trial. Patients with pleural carcinosis, eligible for the surgical management of their pleural effusion can be enrolled. Cisplatin (7.5–12–5–35–70 mg/m2) heated at 39±1 °C is delivered into the thoracic cavity before the surgical effusion management. Initially, the study consists in a dose escalation of the four different cisplatin doses. The primary endpoint is the maximal tolerated dose of cisplatin administered by PITHAC. The secondary and translational endpoints are adverse events and the immune response directed against cancer following PITHAC. There is then an expansion phase at the recommended cisplatin dose on an additional 15 patients with identical outcomes. Discussion: Pressurized intrathoracic delivery of chemotherapy under hyperthermic conditions was never tested so far. We plan to determine the safety of such an approach in patients managed for pleural carcinosis. If proven safe, PITHAC could be combined with systemic immunotherapies for the management of cancer. Trial registration: ClinicalTrials.gov Identifier: NCT06281860